In-depth examination of spatiotemporal figures in open reproducible research. Issue 5 (3rd September 2019) - Konkol, Markus; Kray, Christian
ABSTRACT: Figures such as maps and time series are essential means to visualize spatiotemporal results in scientific papers. Being able to recompute them using the underlying source code and data is thus a core aspect in reproducible research. However, many scientists see the preparation of code and data for publication as an additional burden without immediate benefits. In this work, we investigate advantages and new capabilities of reproducible research papers. Our key contributions are (i) the extension of a geoscientist's workflow while examining papers including reproducible figures such as maps and (ii) the prototypical implementation of the workflow as a web application. The workflow is based on current practices of geoscientists and encapsulates benefits of reproducible figures. It is informed by ideas and needs identified by geoscientists in a survey, interviews, and a focus group. Based on their statements, we first extend the traditional workflow steps Discovery and Inspection by additional capabilities and propose two new steps: Manipulation of the content of a spatiotemporal figure and Substitution of the underlying code and data. The extended workflow and its implementation might facilitate in-depth examination and reusability of geoscientific results.